2018
DOI: 10.1177/1557085118769741
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Identities and Narratives of Motherhood: A Qualitative Exploration of Women’s Pathways Into and Out of Offending

Abstract: Existing research in criminology often focuses on changes in offending behaviors over time. Yet, less is known about the role of gender in women's offending and little consideration is directed toward the integration of gender and parenthood in understanding offending trajectories. This article examines how and when offending and desisting pathways are shaped by motherhood. Interviews were conducted with 37 mothers in New York City with histories of offending behaviors. The data demonstrate how motherhood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Other research has documented such effects in sentencing outcomes (Steffensmeier & Demuth, 2006). Yet, the current study indicated that system-involved women themselves have an awareness of the violation of gendered expectations, similar to prior research (Garcia-Hallett, 2019; Gunn et al, 2018; Sharpe, 2015). Such violations are especially pronounced among mothers as they are expected to be providers and positive role models for their children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other research has documented such effects in sentencing outcomes (Steffensmeier & Demuth, 2006). Yet, the current study indicated that system-involved women themselves have an awareness of the violation of gendered expectations, similar to prior research (Garcia-Hallett, 2019; Gunn et al, 2018; Sharpe, 2015). Such violations are especially pronounced among mothers as they are expected to be providers and positive role models for their children.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have assessed the internalization process of crime-focused labels and subsequent stigma among system-involved women. Although such research is scant, prior studies have demonstrated stigmatization in relation to motherhood and substance abuse, in particular (Gålnander, 2020; Garcia-Hallett, 2019; Gueta & Chen, 2019; Gunn et al, 2018; Sharpe, 2015). Stigmas related to former incarceration and substance abuse counter women’s role expectations related to motherhood and romantic partners (Gunn et al, 2018; Sharpe, 2015).…”
Section: Labeling Theory and Stigmamentioning
confidence: 99%
“…Through a critical race feminist lens, scholarly research has made important contributions in areas focused on incarcerated mothers, mothers of incarcerated children, and adolescent girls of incarcerated parents (Garcia-Hallett, 2019;Hayes-Bautista, 2013;Lopez & Corona, 2012;Mitchell & Davis, 2019). Yet, little attention has been given to how parental incarceration specifically intersects with race, ethnicity, and gender for young women.…”
Section: The Process Of Parental Incarcerationmentioning
confidence: 99%
“…Women of color are forced to survive a racialized “feminization of poverty” that can surface as financially motivated offending behaviors like fraud, theft, and burglary (Carlen, 1988; Garcia-Hallett, 2019). However, the intersectionality of gendered and racial-ethnic disparities in employment are further shaped by the presence of a criminal record, which introduces stereotypes about work ethic and assumptions about people skills, communication skills, and the ability to adapt to diverse work environments (Giguere & Dundes, 2002; Graffam, Shinkfield, & Hardcastle, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The women were most frequently incarcerated for drug crimes (i.e., possession and sale) and money crimes (e.g., identity theft, shoplifting, burglary, and robbery), common among women offenders (McCorkel, 2013; Reiman & Leighton, 2017). The prevalence of monetary crimes is largely attributed to their systematic oppression as a marginalized group with lasting social expectations, while their drug crimes often represent adoptive coping mechanisms to life’s challenges or negative relationships (Garcia-Hallett, 2019). At the time of the interview, the women had various obstacles postincarceration: 68% were unemployed (not including unpaid internships), 78% were living in transitional housing, with family, in shelters or on the street, and half of the mothers with minor children did not have custody.…”
Section: The Current Studymentioning
confidence: 99%